AEROTOXIC SYNDROME AS A MIRCE MECHANICS PHENOMENON - Knežević, Jezdimir (Journal of Applied Engineering Science, 2016)
Aerotoxic syndrome is a somewhat controversial condition that could be triggered by the air compression systems in commercial planes. Some of the air that is compressed and recirculated throughout the cabins originates in jet engines; when excess oil molecules enter that air supply, it can result in what is called a “fume event” Thus, the main objective of this paper is to address the aerotoxic phenomenon as one possible mechnaism of the motion in Mirce Mechanic and examine how some of the existing Mirce Mechanics method could be applied to calculate reduction in the probability of inhaling aerotoxic, by the crew and frequent flyers ,through the application of some of the options available to the designers and operators presented in the paper.
Keywords: Digitalization; Technical Diagnostics; Proactive maintenance; Smart maintentance